2013
DOI: 10.1111/jsm.12203
|View full text |Cite
|
Sign up to set email alerts
|

Current Opinions on Alternative Reservoir Placement for Inflatable Penile Prosthesis among Members of the Sexual Medicine Society of North America

Abstract: Introduction The Sexual Medicine Society of North America (SMSNA) includes as its members the most experienced prosthetic surgeons in North America who implant inflatable penile prostheses (IPPs). Obliteration of the space of Retzius (SOR) resulting from robotic-assisted laparoscopic prostatectomy (RALP) is a growing concern that has prompted many surgeons to look for alternative locations for reservoir placement during IPP implantation. Aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…The increasing popularity of robotic‐assisted laparoscopic prostatectomy (RALP) has added additional challenges to placing a reservoir in the SOR because the space becomes obliterated with this technique [17]. A recent study has shown that 82% of experienced implant surgeons feel that placing a reservoir in the SOR in RALP patients is more difficult [18]. These recent concerns of reservoir placement in the SOR, particularly in RALP patients, have fueled the recent interest in alternative reservoir placement sites.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing popularity of robotic‐assisted laparoscopic prostatectomy (RALP) has added additional challenges to placing a reservoir in the SOR because the space becomes obliterated with this technique [17]. A recent study has shown that 82% of experienced implant surgeons feel that placing a reservoir in the SOR in RALP patients is more difficult [18]. These recent concerns of reservoir placement in the SOR, particularly in RALP patients, have fueled the recent interest in alternative reservoir placement sites.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the reservoir has been placed in the prevesical or retropubic space, also known as the space of Retzius. Although complications are rare, risk of viscous or vascular injury has led some prosthetic surgeons to believe placement in an “ectopic” location, such as anterior or posterior to the transversalis fascia, is advantageous to patient safety ( 48 - 50 ).…”
Section: Methodsmentioning
confidence: 99%
“…Participants reported that IPP reservoirs are either sometimes (46%) or frequently (36%) harder to place in the space of Retzius among robotic-assisted laparoscopic prostatectomy patients and that reservoir placement outside of the space of Retzius is sometimes (54%) or frequently (35%) advantageous for patients' safety. Respondents agreed (97%) that physician-training courses should specifically include content relating to alternative reservoir placement techniques [10].…”
Section: Ectopic Outcomesmentioning
confidence: 99%